1997
DOI: 10.3141/1605-02
|View full text |Cite
|
Sign up to set email alerts
|

Driver Understanding of Alternative Traffic Signs

Abstract: Traffic control devices are intended to promote safe and uniform operation of motorized and nonmotorized traffic using the roadway. Motorists rely on traffic control devices to provide information about traffic laws and regulations, to identify potential roadway hazards, and to provide information to help them find their desired destinations. However, traffic control devices serve little purpose if they are not understood by a significant proportion of the driving population. The findings and recommendations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…However, several had low comprehension levels, indicating that their associated safety message would not be adequately presented to drivers (Picha, Hawkins, Womack, & Rhodes, 1997). Numerous studies have found low comprehension levels for symbols (Caird, Wheat, McIntosh, & Dewar, 1997;Picha et al, 1997;Shinar et al, 2003). In order to improve the sign situation the design of symbols/signs should be based on iterative design principles together with input from samples of the target consumer.…”
Section: Introductionmentioning
confidence: 99%
“…However, several had low comprehension levels, indicating that their associated safety message would not be adequately presented to drivers (Picha, Hawkins, Womack, & Rhodes, 1997). Numerous studies have found low comprehension levels for symbols (Caird, Wheat, McIntosh, & Dewar, 1997;Picha et al, 1997;Shinar et al, 2003). In order to improve the sign situation the design of symbols/signs should be based on iterative design principles together with input from samples of the target consumer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the crossbuck and advance warning sign convey the message that a grade crossing is near, the driver action required and the location of the sign with respect to the grade crossing is not well understood (Bridwell, et al, 1993;Dolan, 1996;Fambro, et al, 1994;Picha, et al, 1997). This section addresses research conducted since the publication of that examined driver understanding of the signs at grade crossings and discusses proposed alternative sign systems to improve driver comprehension.…”
Section: Signsmentioning
confidence: 99%
“…Several studies have examined driver attitudes towards grade crossings and driver comprehension of signs at grade crossings. The results generally show that drivers recognize the warning signs (Dolan, 1996;Global Exchange, 1994;Picha, et al, 1997). In one focus group, participants named the advance warning sign as the most familiar indication of a grade crossing followed by the crossbuck and pavement markings (Dolan, 1996), and participants in another focus group indicated that they considered crossbuck to be the basic marker identifying the location of railroad tracks (Global Exchange, 1994).…”
Section: Crossbuck and Advance Warning Signsmentioning
confidence: 99%
See 2 more Smart Citations